INITIAL ANALYSIS OF STUDENT NEEDS FOR DIGITAL PLATFORM DEVELOPMENT - Netti, Syukma; Hidayat, Hidayat; Zulfadli, Zulfadli; Khairunnisa, Aulia (Study program PGSD FKIP Universitas Bung Hatta, 2022)
Until now, students' behavior in handling waste has not had a broad impact on social life. For this reason, more massive efforts are needed to provide education that has a real impact, namely by creating a digital platform. The purpose of this research is to describe the results of an analysis of the initial needs of elementary school students for the development of digital platforms. Students' needs for the form of display of e-modules in digital platforms that students like and students' views on current waste management. The research method used is survey method. The sample in this study were 397 elementary school students in Padang City. The instrument used is a questionnaire. Data is processed using descriptive statistics. Based on data processing, it was found that the e-module model that was relatively preferred by elementary school students was the e-module which was presented with a composition of lots of writing with few pictures as much as 57%, little writing with lots of pictures as much as 39% and in all written form as much as 4%. When compared to videos, comics and books dominant students prefer in the form of ordinary digital books as much as 43%, in the form of comics 22% and in the form of videos as much as 35%. The behavior of elementary school students in the city of Padang is relatively good in handling waste, more than 63% have disposed of waste in its place. However, segregated waste handling is still low, namely